Characterization of core-shell structured Ni@GDC anode materials synthesized by ultrasonic spray pyrolysis for solid oxide fuel cells. Issue 12 (September 2016) - Lim, Chae-Hyun; Lee, Ki-Tae
Abstract: Core-shell structured NiO@GDC powders with NiO cores and GDC shells were synthesized by ultrasonic spray pyrolysis (USP) with a four-zone furnace. The morphology of the as-synthesized powders can be modified by controlling parameters such as the precursor pH, carrier gas flow rate, and zone temperature. At high carrier gas flow rates, the as-synthesized core-shell structured NiO@GDC powders have raisin-like morphology with a rough surface; this is due to fast gas exhaustion and insufficient particle ordering. The core-shell structured Ni@GDC anode showed considerable electrochemical performance enhancement compared to the conventionally-mixed Ni-GDC anode. The polarization resistance (Rp ) of conventionally-mixed Ni-GDC anodes increases gradually as a function of the operation time. Alternatively, the core-shell structured Ni@GDC anode synthesized by USP does not exhibit any significant performance degradation, even after 500 h of operation. This is the case because the rigid GDC ceramic shell in the core-shell structured Ni@GDC may restrain Ni aggregation.